Singapore Defence Technology Summit – Is the Innovation Winter Coming? - Lockman, Zoe Stanley (2019)
Securing an advantage in emerging technological domains such as artificial intelligence (AI) and 5G means winning the competition for global talent and unrestricted access to supply chains. The accelerating Sino-US strategic competition, however, raises new debates on regulatory regimes and the future diffusion of information and technologies across borders.